Whitening of kaolin-quartz-feldspar dental porcelains by chemical attack using commercial peroxides - Renata Martins Benetti; Mariana de Souza-Pereira; Gécica Cardoso Bellettini de Souza; Fábio Elyseu; Leidy Johanna Jaramillo-Nieves; Adriano Michael Bernardin (Next Materials)
In restorative dentistry, the use of dental ceramics or porcelains are always evolving. The continuous advance in dental restorative materials has resulted in an increase in the use of conventional ceramic restorations due to their color, surface roughness, and strength. However, the whitening procedure currently used for teeth has no effect on the porcelain of dentures, veneers, and dental contact lenses. Therefore, the aim of this work was to determine the effect of whitening agents on the aesthetics and mechanical behavior of porcelain ceramic compositions. Kaolin, quartz, and sodium-potassium feldspar were used as raw materials according to a mixture design. After mixing, the compositions were uniaxially pressed (35 MPa) and sintered at 1100 °C for 4 h. After sintering, the physical characteristics (density, water absorption and dimensional change), mechanical behavior (Vickers hardness and tensile strength) and microstructure (SEM and XRD) of the samples were evaluated. The whitening of the compositions was determined by colorimetry (L* coordinate). The results showed that the dental ceramic compositions had similar properties to that of natural dental structures and were susceptible to whitening by the commercial agents used.